The Effects of Rice Husk Ash as Bio-Cementitious Material in Concrete - Mays Mahmoud Alsaed; Rafal Latif Al Mufti (Construction Materials)
Concrete is one of the most commonly used materials in civil engineering construction, and it continues to have increased production. This puts pressure on the consumption of its constituent materials, including Portland cement and aggregates. There are environmental consequences related to the increased emission of CO2 that are associated with the production process of Portland cement. This has led to the development and use of alternative cementitious materials, mainly in the form of condensed silica fume, pulverised fuel ash, and ground granulated blast furnace slag. All of these are by-products of the silicon, electrical power generation, and iron production industries, respectively. In recent years, attention has turned to the possible use of sustainable bio-waste materials that might contribute to the replacement of Portland cement in concrete. This research investigates the effects of using rice husk ash as cement replacement material on the 1 to 28-day concrete properties, including the compressive strength, workability, and durability of concrete. The findings indicate that including rice husk ash in concrete can improve its strength at 3–28 days for percentage replacements of 5% to 20% (ranging from 2.4% to 18.7% increase) and improvements from 1 day for 20% replacement (with 11.1% increase). Any percentage replacement with rice husk ash also reduced the air permeability by 21.4% and therefore improved the durability, while there was a small reduction in the workability with increased replacement.